Materialität - Digitalisierung - Bildung - Leineweber, Christian; Waldmann, Maximilian; Wunder, Maik (Verlag Julius Klinkhardt, 2023)
The anthology is guided by the question of whether the digital sphere exhibits a materiality. Answers are explored within the horizon of the basic educational concept of education. Based on different theoretical approaches, the volume includes references to media pedagogy and media didactics as well as contributions from childhood pedagogy, historical pedagogy, aesthetic education, inclusion pedagogy, educational gender studies, school pedagogy, adult education, and empirical and theoretical educational research. In this way, diverse conceptualizations of education are proposed and contextualized, recognizing the interplay of materiality and digitalization as a space of reflection for their thinking.